Unlocking the potential of embryos: insight of systematic review and meta-analysis into laser-assisted hatching’s role in conquering recurrent implantation failure - Tingting Du; Yang Ma; Zanche Huang; Xiaoxuan Zhao; Qin Zhang; Ning Ren (Frontiers in Reproductive Health)
IntroductionThe journey of assisted reproductive technology (ART) for couples facing recurrent implantation failure (RIF) is fraught with emotional and physical challenges. RIF, often characterized by the failure of high-quality embryos to implant after multiple ART cycles, has directed attention towards interventions like laser-assisted hatching (LAH). However, discrepancies in the literature necessitate a comprehensive review of LAH's efficacy and safety.Materials and methodsFollowing a thorough search of PubMed, Embase, Cochrane, and Web of Science databases up to November 2023, retrospective studies or RCT were considered for inclusion. Summary effect sizes [odds ratio (OR) or risk ratio (RR) with 95% confidence interval (CI)] were calculated for each outcome.Results and conclusionEight studies comprising 2,634 patients were included. LAH significantly improved implantation rates (OR: 1.26, 95% CI: 1.05–1.51). Clinical pregnancy rates increased in patients who had fresh embryos transferred (OR: 1.29, 95% CI: 1.05–1.58). Notably, LAH was associated with higher miscarriage rates in frozen embryo transfers (OR: 1.45, 95% CI: 1.04–2.02). No significant increase in ectopic or multiple pregnancy rates was observed. For patients with RIF, especially older women, LAH presents a potential avenue to improve implantation. Its impact on clinical pregnancy rates is less substantial. However, its impact on final live birth rates and the increased miscarriage risk in frozen transfers necessitate a cautious and individualized approach. The technique's safety, while generally upheld, requires careful application and consideration of the specific challenges RIF patients face. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/view/CRD42024497329, PROSPERO (CRD42024497329).